Pengaruh Beban Kerja Dan Kompensasi Terhadap Produktivitas Kerja Karyawan di PR. Makmur (International Forum of Researchers and Lecturers, 2023)
This study aims to determine how the influence of workload and compensation on work productivity in PR. Makmur. Respondents in this study were PR. Makmur production employees. In this study using primary data obtained from distributing questionnaires and secondary data obtained from PR.Makmur companies. The analytical method used in this study is multiple linear analysis. The results of this study indicate that workload has a significant effect on employee work productivity, compensation has a significant effect on work productivity and workload and compensation simultaneously have a positive and significant effect on employee produktivity. This means that when the workload and compensation is high, the work produktivity of employees will increases